2016
DOI: 10.1080/19336918.2016.1159380
|View full text |Cite
|
Sign up to set email alerts
|

The ciliary GTPase Arl13b regulates cell migration and cell cycle progression

Abstract: The GTPase ARL13B is localized to primary cilia; small cellular protrusions that act as antennae. Its defective ARL13B hennin (HNN) variant is linked causally with Joubert Syndrome, a developmental ciliopathy attributed to poor sensing of extracellular chemical gradients. We tested the hypothesis that impaired detection of extracellular voltage gradients also contributes to the HNN phenotype. In vitro, extracellular electric fields stimulated migration of wild type (WT) and HNN fibroblasts toward the cathode b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 68 publications
3
15
0
Order By: Relevance
“…Moreover, PC are known to be involved in other developmental aspects that could contribute to defective neurogenesis and CNS cell migration, often involving PC's close association with the centrosome and the Golgi apparatus. These involve SHH (9294) and Platelet Derived Growth Factor (9598) signalling, and governance of cell migration (4, 8, 9, 50, 63, 99102) and cell division (9597, 103110) through sensing extracellular cues. This last point is exemplified by the fact that serum withdrawal during cell culture is a ciliogenic condition (97, 103, 105, 109), indicating that cells may use their cilia to ensure that the extracellular conditions are right for mitosis initiation.…”
Section: Neurodevelopmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, PC are known to be involved in other developmental aspects that could contribute to defective neurogenesis and CNS cell migration, often involving PC's close association with the centrosome and the Golgi apparatus. These involve SHH (9294) and Platelet Derived Growth Factor (9598) signalling, and governance of cell migration (4, 8, 9, 50, 63, 99102) and cell division (9597, 103110) through sensing extracellular cues. This last point is exemplified by the fact that serum withdrawal during cell culture is a ciliogenic condition (97, 103, 105, 109), indicating that cells may use their cilia to ensure that the extracellular conditions are right for mitosis initiation.…”
Section: Neurodevelopmentmentioning
confidence: 99%
“…A possible explanation involves the dysregulation of WNT signalling important for the appropriate differentiation of dopaminergic neurons (163). The WNT pathway also regulates dopaminergic neural progenitor cell migration during electrotaxis (62); the health of PC has been shown to affect electrotaxis in fibroblasts (63), though studies in neurons are lacking. Moreover, dopamine signalling has been found to affect PC length in striatal neurons (160).…”
Section: Primary Cilia and Dopaminementioning
confidence: 99%
“…Non-muscle myosin heavy chain IIA (also known as Myh9) was identified as an Arl13b effector that was necessary for Arl13b and actin interaction, and consequently for circular dorsal ruffles formation and cell migration (Casalou et al, 2014). Other studies showing the defective migration of interneurons in Arl13b knockout mice as well as in fibroblasts from the hennin mice support the role of Arl13b in cell migration (Higginbotham et al, 2012;Pruski et al, 2016).…”
Section: Arl13bmentioning
confidence: 76%
“…The efficiency of the shRNA-mediated silencing was confirmed by RT-qPCR and immunoblotting (Figure S1A,B). Since we and others observed that Arl13b silencing impairs cell growth (Figure S1C; [13,14,18]), we used mitomycin C to inhibit cell proliferation and exclude proliferation interference in migration and invasion assays lasting for more than 8 hours. Mitomycin C efficiency was confirmed by monitoring the number of viable cells (Figure S1D).…”
Section: Resultsmentioning
confidence: 99%